PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA KARTU TRUTH OR DARE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD GUGUS V KECAMATAN SERIRIT - Putu Lilis Ayu Artini; I Made Sedana; I Nyoman Pancaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of the implementation of the Think Pair Share (TPS) cooperative learning model integrated with Truth or Dare cards on the critical thinking skills of fifth-grade students of Elementary School Cluster V, Seririt District. This study uses a quasi-experimental method through a quantitative approach. Data collection techniques applied include observation, in-depth interviews, critical thinking ability tests, and documentation studies. The research subjects consisted of 22 fifth-grade students at SDN 1 Gunungsari who were designated as the experimental group. The results of the study revealed a significant increase in students' critical thinking skills. This is evidenced by the average pre-test score of 45.209 which increased drastically to 83.300 at the post-test. Statistical analysis using the independent t-test showed a significance value (Sig.) of 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05). These findings confirm a significant difference between the experimental group and the control group after the treatment. Based on these results, it can be concluded that the implementation of the TPS model assisted by Truth or Dare cards has a positive and significant impact on improving students' critical thinking skills in IPAS Education. Therefore, this combination of learning models and media is recommended as an innovative alternative for elementary school educators to optimize students' critical thinking potential in the classroom.